2008
DOI: 10.1136/vr.162.24.777
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, clinicopathological and histological changes observed in 14 cats treated with glucocorticoids

Abstract: Fourteen cats were given immunosuppressive doses of either prednisolone (4.4 mg/kg/day) or dexamethasone (0.55 mg/kg/day) for 56 days. Complete blood counts, serum biochemistry profiles and urinalyses were performed on days 0 and 56, and liver biopsies were taken laparoscopically on day 56, because of evidence of hepatic disease on the serum biochemistry profiles. There were significant increases in the cats' mean white blood cell counts, neutrophil counts and monocyte counts, and significant decreases in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
17
0
6
Order By: Relevance
“…for 8 days resulted in reduced glucose tolerance after an IV glucose load in all six cats, and three of the six developed hyperglycemia (Middleton and Watson, 1985). It has been suggested that dexamethasone has greater diabetogenic effects than equipotent doses of prednisolone (Lowe et al, 2008;. Steroid diabetes often goes into remission, provided that the glucocorticoid application is ceased immediately and insulin treatment is initiated.…”
Section: Exogenous Glucocorticoids and Progestinsmentioning
confidence: 98%
“…for 8 days resulted in reduced glucose tolerance after an IV glucose load in all six cats, and three of the six developed hyperglycemia (Middleton and Watson, 1985). It has been suggested that dexamethasone has greater diabetogenic effects than equipotent doses of prednisolone (Lowe et al, 2008;. Steroid diabetes often goes into remission, provided that the glucocorticoid application is ceased immediately and insulin treatment is initiated.…”
Section: Exogenous Glucocorticoids and Progestinsmentioning
confidence: 98%
“…When treated for 9 weeks or longer, most cats continued to have no or few clinical signs (Lowe et al, 2008). Some cats with iatrogenic cortisol excess developed hepatomegaly, muscle wasting, ecchymoses, and skin fragility (Scott et al, 1979;Lowe et al, 2008). Some cats with iatrogenic cortisol excess developed hepatomegaly, muscle wasting, ecchymoses, and skin fragility (Scott et al, 1979;Lowe et al, 2008).…”
Section: Etiology Iatrogenic Cushing's Syndromementioning
confidence: 99%
“…11-2). Glucocorticoids have many immunosuppressive effects, including decreased macrophage expression of inflammatory cytokines, increased expression of some antiinflammatory cytokines, decreased function and maturation of dendritic cells, decreased T cell activation and proliferation in response to mitogens, decreased cell-mediated lysis of target cells, decreased mitogeninduced B cell proliferation, and decreased antibody production (Tuckermann et al, 2005;Lowe et al, 2008). Are these cats grooming normally but causing hair loss, thereby also causing owner concern or are they grooming more than usual?…”
Section: Dermatologic Abnormalitiesmentioning
confidence: 99%
“…Associated signs occur most often after repeated injections of long-acting glucocorticoid preparations; however, occurrence of signs (e.g., polyphagia and weight gain) have also been reported after a single injection of methylprednisolone acetate (Ferasin, 2001). Unique to the cat is the development of spontaneous tearing and sloughing of the skin and, in rare cases, medial curling of the pinnae (Scott et al, 1982;Lowe et al, 2008a;2008b). Although this may be true for the majority of cases, polyuria and polydipsia have also been reported in cats without diabetes (Lien et al, 2006;Lowe et al, 2008a).…”
Section: Iatrogenic Hyperadrenocorticismmentioning
confidence: 99%
“…Serum bile acids may also increase during glucocorticoid therapy, whereas ammonia tolerance test does not seem to be affected (Meyer, 1982;DeNovo and Prasse, 1983;Solter et al, 1994). The ALP activity may also increase; however, it often still remains within the normal range (Scott et al, 1982;Sharkey et al, 2007;Lowe et al, 2008b). Otic medications containing triamcinolone or dexamethasone were also associated with an increase in ALP, ALT, and GGT (Meyer et al, 1990;Abraham et al, 2005).…”
Section: Laboratory Abnormalitiesmentioning
confidence: 99%